Effectiveness evaluation of an organisational intervention, targeting pregnancy and addiction care professionals, among women who have just given birth in maternity wards and smoked tobacco during pregnancy (5A-QUIT-N): study protocol for a stepped-wedge cluster randomised trial - Fleur Delva; Patrick Brochard; Marc Auriacombe; Charlotte Kervran; Linda Cambon; François Alla; Melina Fatseas; Judith Martin-Fernandez; Rachid Salmi; Dominique Dallay; Marion Kret; Loïc Sentilhes; et al. (BMJ Open)
Introduction In 2021, among French women who smoked when they knew they were pregnant, 59% still smoked at the end of pregnancy. Support for pregnant women to stop smoking must include a structured organisational perspective. The main objective of the study is to evaluate the effectiveness of the 5A-QUIT-N organisational intervention on smoking cessation at delivery among pregnant women who smoke during pregnancy.Methods and analysis The overarching goal of the 5A-QUIT-N intervention, which aims to organise the healthcare professionals monitoring pregnancy, specialists in addiction and tobacco use, and clinical and training tools, using the 5As method. The 5A-QUIT-N intervention will be evaluated in a pragmatic stepped-wedge cluster randomised trial. Within each cluster, during the 6 months before (control) and after (intervention) the intervention, women who smoke tobacco during pregnancy will be enrolled during their maternity stay after delivery. A transition period is planned between the control and intervention periods to deploy the intervention. All participating women will be interviewed using a heteroquestionnaire to assess smoking cessation, tobacco use monitoring by healthcare professionals and individual factors associated with tobacco use during pregnancy. The primary outcome was the point prevalence of abstinence at delivery, which is the proportion of women reporting abstinence from smoking for at least 7 days at delivery. 4200 women who smoked tobacco during pregnancy will be recruited over the entire study period (33 months) to evaluate the effectiveness. An estimated 4585 participants will be included for all aims.Ethics and dissemination The study will be implemented in accordance with French regulations. The study including the consent process has been independently reviewed and approved by the French ethical board ‘CPP Ile de France I’ on 10 February 2022 (No CPPIDF1-2022-DI08-cat.2). The results will be disseminated on various academic and non-academic platforms. The results will be reported in international peer-reviewed journals and presented at international and national conferences.